V. Gordon Childe and the vocabulary of revolutionary change - Greene, Kevin
Because Childe wrote extensively for non-archaeologists and the public his Neolithic and Urban Revolutions have continued to influence historians in general Ñ and historians of technology in particular Ñ into the 1990s. This paper examines their influence, while noting significant changes in Childe's terminology and use of analogy between 1928 and 1957.